Aestivation in apple leafcurling midge (Diptera Cecidomyiidae) parasitoid Platygaster demades Walker (Hymenoptera Platygastridae) - He, X.Z.; Wang, Q. (New Zealand Plant Protection, 2007)
This study reports an investigation on the aestivation and overwintering strategies of Platygaster demades an egg parasitoid of apple leafcurling midge (ALCM) Dasineura mali under natural conditions during 2005 2006 The first three generations of ALCM developed into adults during the springautumn of 2005/2006 and the fourth generation overwintered as larvae All first generation P demades emerged in the spring of 2005 About 64 of live individuals of P demades in the second generation and 38 in the third generation entered aestivation as eggs which hatched in mid March and early May 2006 respectively Parasitoid eggs of the fourth generation started to hatch four weeks after the parasitised ALCM larvae entered the soil The aestivated and fourth generation parasitoids overwintered as immature stages and started emerging in late September 2006 The emergence patterns of overwintered parasitoids and ALCM were highly synchronized in the following season